Concurrent Infection of Infectious Bronchitis (IB) and Sub-Clinical Infectious Bursal Disease (IBD) in an Organised Poultry Farm - Krithiga, K.; Devi, S. S.; Shankar, Surya; Reshma, P. S.; Abraham , M. J.; Nair, Divakaran (International Journal of Livestock Research, 2019)
Four carcasses of 4-5 days old commercial broiler chicks were submitted for post-mortem examination to the Department of Veterinary Pathology, College of Veterinary and Animal Sciences, Mannuthy, Thrissur. The owner reported 60% mortality in that flock. On necropsy examination, chalky deposits on the pericardium, liver and in mesonephric tubules of the kidneys were observed. Histopathological examination revealed focal pneumonia and congestion in lungs, uric acid pericarditis, fatty degeneration with capsular thickening in liver, degeneration and uric acid crystals in the renal tubules. Spleen and bursa of Fabricius revealed lymphoid depletion. Reverse-transcriptase polymerase chain reaction (RT-PCR) carried out with the pooled tissue samples gave positive results for both Infectious Bronchitis (IB) and Infectious Bursal Disease (IBD). The nephrogenic form of IB would have resulted in nephrosis, uric acid pericarditis and perihepatitis. Though the Bursa of Fabricius did not reveal any striking gross pathology, the histopathological changes and positive PCR results for IBD suggest a sub-clinical infectious bursal disease virus (IBDV) infection.